MODEL DEVELOPMENT SURVIVAL RESILIENCE OF FASHION SMES IN BANDUNG POST COVID-19 PANDEMIC - Anggraini, Westi
The Covid-19 pandemic has significantly impacted economies both in Indonesia and globally, leading to substantial income declines and shifts in business phenomena. This situation necessitates Small and Medium Enterprises (UMKM), particularly those in the fashion sector, to respond to changes and overcome the crisis by understanding resilience models. Fashion UMKM is a major contributor to Indonesia's economy, yet there is a lack of research on resilience models for these businesses post-Covid-19. This study aims to develop a resilience model for fashion UMKM after the pandemic. This research employs a quantitative approach and utilizes non-probability sampling, specifically purposive sampling. Data is gathered from 170 fashion UMKM in Bandung through a questionnaire containing 41 indicators to measure eleven research variables. The data is processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.2.9 software. The research findings indicate that marketing innovation, financial resources management, adequate material supply, customer relationship management, market knowledge, innovation digitalization technology, and entrepreneurial self-efficacy have a positive and significant impact on the resilience of fashion UMKM in Bandung. However, company adaptability & flexibility do not significantly affect the resilience of fashion UMKM in Bandung post-Covid-19. Additionally, the study reveals that the impact of Covid-19 significantly negatively affects company performance and moderates the relationship between resilience and business performance of fashion UMKM in Bandung. This research contributes conceptually and empirically to the literature on resilience models for fashion UMKM post-Covid-19. Practically, the study implies that educating UMKM stakeholders on applying resilience models is crucial for developing appropriate strategies to help fashion UMKM survive the transition period after the Covid-19 pandemic.